Model Hubungan Kerja Kepala Desa dengan Badan Permusyawaratan Desa dalam Penyelenggaraan Pemerintahan Desa - Febriyanti Tabi, Maria; Pradana, I Putu Yoga Bumi; Kase, Petrus (Policy, Law and Political Research Center, 2024)
This research aims to determine the model of the Village Head's working relationship with the Village Consultative Body (BPD) in administering village government and the factors inhibiting the Village Head's working relationship with the BPD in administering the Golo Lero Village government. So, the research method used in this research is descriptive qualitative. Data collection uses observation, interview and documentation techniques. Data analysis uses interactive data analysis, according to Miles and Huberman. The results of this research show that the working relationship model between the Village Head and the BPD in administering Village Government is the Dominative Model and the Conflictual Model because in discussing and agreeing on village regulations, the village head is very dominant in making or determining village regulations as well as the opinions and decisions made by the Village head is absolute and becomes a final decision. As a village legislative institution, the BPD has a vital role in formulating village regulations but is often absent in the formulation or enactment of village regulations. It was also found that several inhibiting factors were in implementing the Village Head's working relationship with the BPD, namely conflicts of interest, Village Election Resentment, low quality of Human Resources, and low BPD allowances.